Mechanical Properties Enhancement of AZ91 Magnesium Alloy Reinforced with Various Ratios of Titanium Particles and Processed by ECAP (Journal of Research Updates in Polymer Science, 2023)
This study utilized AZ91 magnesium-aluminum alloy as the matrix for magnesium-based composites, reinforced with micron-sized titanium (Ti). Gravity casting and mechanical stirring were employed to fabricate specimens with 0 wt.%, 0.3 wt.%, and 0.5 wt.% Ti reinforcement. Heat-treated samples underwent Equal Channel Angular Pressing (ECAP), and microstructures were analyzed via SEM and XRD. The experimental results demonstrate that the addition of micron-sized titanium improves the yield strength, ultimate tensile strength, and hardness. The inclusion of 0.5 wt.% titanium powder resulted in a 17.5% increase in ultimate tensile strength and a 37% increase in yield strength. After secondary processing with ECAP, the ultimate tensile strength showed an additional 25% increase, while the yield strength increased by 13.5%. Vickers hardness test results reveal a significant 13.7% strength improvement with the addition of 0.5 wt.% titanium powder, and after ECAP secondary processing, there was a marginal additional increase of 0.8%.